Creating Legal Unity in a Rapidly Changing World: Indonesia and the Netherlands Compared - Huis, Stijn Cornelis van (E3S web of conferences, 2023)
Confronted with rapid and complex changes in the digital era, both the Indonesian and Dutch Supreme Court have been granted the powers of providing legal solutions at an early stage of the legal process. The Dutch Parliament introduced the Law on Prejudicial Questions whereas the Indonesian Supreme Court reinstated the chamber system. Each year, pressing legal issues are discussed by the Supreme Court judges in the chambers and the legal solutions published in a circular ( Surat Edaran Mahkamah Agung , SEMA) as guidelines to be followed by lower courts. In this paper we compare both ‘legal shortcuts’ and argue that, while the goal of legal unity is an urgent issue in Indonesia, to be able to properly function as legal guidelines for judges and lawyers SEMA require a more detailed description of the legal issue and legal reasoning behind the offered legal solutions.